EKSISTENSI PUBLIC SPHERE DALAM MEDIA MAINSTREAM: Studi pada Rubrik Citizen Journalism Tribun Yogyakarta - Yanti Dwi Astuti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
Citizen Journalism phenomenon became a trend in the world of journalism and became a new public space for society. One of the mainstream media that is Tribun Jogja newspaper adopted the trend into its rubric called Citizen Journalism rubric. In practice, however, there is an enormous amount of preaching incompatible with the essential meaning of citizen journalism and the public space itself. Where it tends to be very flat and descriptive does not touch on the essence of the meaning of public space is the discussion process that prioritizes rational and critical debate and still apply the process of screening and editing by editors. This is in stark contrast to the spirit of the presence of citizen journalism that is free from any intervention, freely voicing opinions, interactivity, unlimited space, no competition between authors, and no strict detection of news content. Based on this assumption, this research will try to uncover how the existence of public space through Citizen Journalism rubric of Tribun Jogja in the period of one year since its presence which is from 2011 to 2012. Data obtained through in-depth interviews and documentation in the form of Citizen Journalism rubric in Tribun Jogja. Data analysis using three stages of discourse analysis on the news consisting of text analysis, social cognition, and social context. This study reinforces the fact that mainstream media is not a free and neutral channel, but a tool of dominant groups and also produces dominant ideologies. So put the rubric named citizen journalism into utopia. Recommendations for editors Citizen Journalism and Koran Tribun Jogja, should provide more news coverage space both in print and online editions, and submit the management of Citizen Journalism rubric to outsiders who have no direct ties with the media concerned, so that the dimension of independence can Achieved.Fenomena Citizen Journalism menjadi trend dalam dunia jurnalisme dan menjadi ruang publik baru bagi masyarakat. Salah satu media mainstream yaitu koran Tribun Jogja mengadopsi tren tersebut ke dalam rubriknya yang dinamakan rubrik Citizen journalism. Namun dalam prakteknya, terdapat banyak sekali kecenderungan pemberitaan yang tidak sesuai dengan makna hakiki dari citizen journalism dan ruang publik itu sendiri. Dimana cenderung sangat datar dan deskriptif tidak menyentuh pada esensi dari makna ruang publik yaitu pada proses diskusi yang megedepankan debat rasional dan kritis serta masih diberlakukannya proses penseleksian dan editing oleh redakturnya. Hal ini sangat kontras dengan semangat hadirnya citizen journalism yang bersifat bebas dari intervensi siapapun, menyuarakan pendapat secara leluasa, interaktifitas, tidak terbatasi oleh halaman (unlimited space), tidak ada persaingan antar penulis, dan tidak adanya penseleksian ketat terhadap konten beritanya. Berdasarkan asumsi tersebut penelitian ini akan mencoba membongkar dan menggambarkan bagaimana eksistensi ruang publik melalui rubrik Citizen Journalism Tribun Jogja dalam kurun waktu tiga tahun sejak kehadirannya yaitu mulai 2011 hingga 2012. Penelitian ini menguatkan fakta bahwa media mainstream bukanlah saluran yang bebas dan netral, melainkan sebuah alat dari kelompok dominan dan juga memproduksi ideologi dominan. Sehingga menempatkan rubrik yang bernama citizen journalism menjadi utopia. Rekomendasi bagi redaktur rubrik Citizen Journalism dan Koran Tribun Jogja, sebaiknya memberikan space pemberitaan rubrik ini lebih banyak lagi baik pada edisi cetak maupun online, dan menyerahkan pengelolaan rubrik Citizen Journalism pada pihak luar yang tidak memiliki ikatan langsung dengan media yang bersangkutan, sehingga dimensi independensi dapat tercapai.